2001
DOI: 10.1071/rd01076
|View full text |Cite
|
Sign up to set email alerts
|

Bait-delivered cabergoline for the reproductive control of the red fox (Vulpes vulpes): estimating mammalian non-target risk in south-eastern Australia

Abstract: Cabergoline (CAB) is a potent dopamine agonist and an inhibitor of prolactin (PRL). In red foxes (Vulpes vulpes), a single oral dose of 100 g kg–1 CAB can cause abortions and postnatal cub mortality from at least Day 21 of the 52-day pregnancy. The abortifacient activity of CAB is owing to the suppression of PRL, which is essential for luteotrophic support in some eutherian species. Postnatal cub mortality probably results from a reduction in the development of the mammary ductile system, which is also partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…Our study suggests that all species that weigh less than the heaviest eastern quoll will be unlikely to trigger an ejector with an activation force set at 26.46 N. A number of field studies on mainland Australia and Tasmania have recorded maximum body weights that are significantly lower than the 7 kg published for spotted-tailed quolls (Edgar 1988 The red fox is seasonally monoestrous, and the vixen will produce a single litter each year after a 52-53-day gestation period (Ryan 1976;Lloyd and Englund 1973;Coman 1983;McIlroy et al 2001). In south-eastern Australia births may occur over a three-month period from late August to November (Marks 2001a) and juveniles <3 kg in mass may be recovered typically from October through to December once they become independent of the natal den. During this period there may be juveniles that are unable to trigger the device.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study suggests that all species that weigh less than the heaviest eastern quoll will be unlikely to trigger an ejector with an activation force set at 26.46 N. A number of field studies on mainland Australia and Tasmania have recorded maximum body weights that are significantly lower than the 7 kg published for spotted-tailed quolls (Edgar 1988 The red fox is seasonally monoestrous, and the vixen will produce a single litter each year after a 52-53-day gestation period (Ryan 1976;Lloyd and Englund 1973;Coman 1983;McIlroy et al 2001). In south-eastern Australia births may occur over a three-month period from late August to November (Marks 2001a) and juveniles <3 kg in mass may be recovered typically from October through to December once they become independent of the natal den. During this period there may be juveniles that are unable to trigger the device.…”
Section: Discussionmentioning
confidence: 97%
“…The resulting regression equation with 95% confidence estimate was used to predict the maximum anticipated mass that could be displaced by each of 31 quadrupedal PBC mammals identified by Marks (2001a) on the basis of the highest recorded body mass for each (Strahan 1988). Data were back-transformed and pulling-force data were expressed in Newtons (N) by multiplying the mass displaced by the gravitational constant (9.8).…”
Section: Predicting Mammalian Target-specificity Of the M-44 Ejector mentioning
confidence: 99%
“…Some smaller quolls (≤2.5 kg) will potentially be able to access and consume the bait, but are believed to be unable to trigger the ejector. Of the 31 potentially bait-consuming native species in south-eastern Australia proposed by Marks (2001), only very large mountain brushtail (Trichosurus caninus) and common brushtail (T. vulpecula) possums remain potential non-target species that could generate enough pulling force to trigger the ejector. The dingo (Canis familiaris dingo) is a target species for control on much of mainland Australia (Fleming et al 2001), but a non-target species in some Target Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One principal weakness of toxicant delivery with conventional meat baits is its relative lack of species-specificity. Thirty-one native carnivores, including some threatened species, are considered to be potentially bait-consuming species in southeastern Australia and may be exposed to bait toxicants even if the hazard of this exposure remains difficult to quantify (Marks 2001). In Victoria, this problem is partly addressed by burying 1080 baits, but not all non-target species are excluded by this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations in four species of marsupial from diverse families showed that cabergoline did not affect reproduction (Hearn et al 1998). An analysis of 25 marsupial and nine eutherian bait-taking species indicated that cabergoline baiting for fox control was unlikely to affect reproduction in these non-target species because of differences in breeding season and a lack of a role for prolactin in these species (Marks 2001).…”
Section: Introductionmentioning
confidence: 99%